Comparative Characteristics Of Ferrokinetic Parameters And Their Relationship With Inflammation In Patients With CHF In Advanced And Senile Age - Akhmedova N.Sh; Abdullaeva U.K.; Musulmanova D.F. (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
To perform a comparative analysis of anemia of chronic disease (ACD) and iron-deficiency anemia (IDA) in late middle-aged and elderly patients with chronic heart failure (CHF) by ferrokinetic parameters, inflammation indexes, and their associations. Materials and methods. 65 patients with ischemic heart disease were evaluated, including 35 patients with CHF and ACD, 10 patients with CHF and IDA, and 20 patients without CHF, ACD, and IDA (control group, CG). Results. Patients with CHF and IDA had true iron deficiency whereas 54% of patients with CHF and ACD had functional iron deficiency, and 46% of patients had no iron deficiency. Levels of acute phase proteins, ferritin and hepcidin, C-reactive protein (CRP), and interleukin-6 (IL-6) were highly significantly different in patients with CHF and ACD and patients with CHF and IDA; positive and significant correlations were found for levels of IL-6 and ferritin, IL-6 and CRP, and CRP and hepcidin. In patients with CHF and IDA, levels of acute phase proteins, ferritin and hepcidin, CRP, and IL-6 were low and correlations of IL-6 with ferritin, IL-6 with CRP, and CRP with hepcidin were non-significant. Concentrations of erythropoietin were significantly higher in patients with CHF and ACD and patients with CHF and IDA compared to the control group; however, significant differences between them were absent.